Influence of the hydrodynamic efforts on the efficiency of the regeneration of the granular filtering material in a water treatment plant - BACHAROU, Taofic; KANHO, Jesugnon Ezéchias; GUENE, Razack; WOROU, Chabi Noel (My University, 2022)
This article aims to study the hydrodynamic conditions of the parameters that influence the removal of dirt particles and aggregates by the drainage of wash water into filter materials for better regeneration efficiency. The water treatment plant with a nominal capacity of 600 m3·h1 is located in the city of Parakou in Benin. It appears that one of the causes of the poor performance of the methods used for water treatment is the insufficient value of the shear stresses of the movement created by the flow of washing water in the filter bed. The use of hydro-elevators and hydrocyclones for the removal of particles from the surface of the grains of the filtering material under hydraulic load makes it possible to reduce the quantity of remaining pollution respectively by 1.5 to 2.5 times compared with the combined washing of water and air. To this end, the performance of grain washing in the hydrocyclone is explained by the presence of centrifugal field, self-separation and the friction of the particles between themselves and on the wall of the apparatus. The regeneration of the filter material under the action of ultrasonic waves reduces the remainder of particles compared to washing with water and air about 6 times.
Keywords: granular filter; regeneration; wash water; water treatment plant; yield